2015
DOI: 10.1039/c5ta04351d
|View full text |Cite
|
Sign up to set email alerts
|

Novel amphoteric ion exchange membranes by blending sulfonated poly(ether ether ketone)/quaternized poly(ether imide) for vanadium redox flow battery applications

Abstract: For vanadium redox flow battery (VRB) applications, novel amphoteric ion exchange membranes (AIEMs) are prepared using sulfonated poly(ether ether ketone) (SPEEK) and quaternized poly(ether imide) (QAPEI) by a facile method. Different from other AIEMs synthesized by multiple steps, SPEEK/QAPEI (S/Q) membranes are directly prepared by blending. It offers a reduction in cost and leads to a high degree of micro-phase separated structure which could facilitate ion transport. The mechanical properties, thermal stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 39 publications
0
51
0
Order By: Relevance
“…22,25 Therefore, it is significant to improve the mechanical durability and chemical stability of the SPEEK membrane to meet the demand of VFB. To accomplish this goal, various strategies have been used, such as incorporating inorganic llers, 26,27 blending with other polymers, 28,29 and reinforcing by porous skeletons. 30 Compared with above microscopic modication approaches, macroscopic protection is another effective method.…”
Section: Introductionmentioning
confidence: 99%
“…22,25 Therefore, it is significant to improve the mechanical durability and chemical stability of the SPEEK membrane to meet the demand of VFB. To accomplish this goal, various strategies have been used, such as incorporating inorganic llers, 26,27 blending with other polymers, 28,29 and reinforcing by porous skeletons. 30 Compared with above microscopic modication approaches, macroscopic protection is another effective method.…”
Section: Introductionmentioning
confidence: 99%
“…50 Liu et al reported that SPEEK and quaternized poly(ether imide) could be mixed to prepare AIEMs. 51 The resulting AIEMs exhibited better vanadium ion resistance than SPEEK and Naon117 and maximum EE of 88.45% in VRBs. He's group explored a number of AIEMs obtained from SPEEK and imidazolium-based PSF, which possessed close area resistance and lower vanadium permeability compared with Naon212.…”
Section: Introductionmentioning
confidence: 90%
“…The VRB performance of Q/S-x was compared with that of various AIEMs reported in the current literatures. 32,34,37,39,[46][47][48][50][51][52][53][74][75][76][77][78][79] At both low and high currents, Q/S-1.37 exhibited increased CE (>96.0%), thus revealing good vanadium ion resistance. Despite varied experimental conditions in different labs, the VE and EE values of Q/S-1.37 at both low and high currents remained at a relatively high level.…”
mentioning
confidence: 99%
“…Open circuit voltage (OCV) measurements can be used to indirectly measure the vanadium ion cross-over [36], as the cross-over through the membrane results in self-discharge, which corresponds to a OCV drop in the performance of the VRFB [37]. Thus, self-discharge was monitored as a function of time.…”
Section: Vanadium Redox Flow Battery Evaluationmentioning
confidence: 99%